BORN FREE AND EQUAL: The History of the Universal Declaration of Human Rights - Christensen, Hanne (Advances in Social Sciences Research Journal, 2020)
This article outlines the process at the United Nations, which resulted in the human rights regime, initiated by the Universal Declaration of Human Rights of 10 December 1948. It analyzes reactions and input from major players. It reveals that the human rights legislation regime was a negotiated member state endeavor with input from various countries across continents, cultures, and religions. It demonstrates the importance of small states in getting the human rights legislation adopted as international law. It refutes the notion that the human rights regime is a western project.